(untitled) (Research, Society and Development, 2020)
This article aimed to survey and analyze the main Brazilian laws regarding indigenous education; briefly conceptualize indigenous school education and indigenous education. It addresses the importance of initial and continuing education for indigenous teachers and their legal support and finally discusses the use of information and communication technologies in the indigenous educational environment as a resource for strengthening their cultures. For this, it uses a methodology based on a qualitative and dialectic approach through document analysis and bibliographic study. At the end, it weaves the final considerations on the themes approached based on the selected authors and the analyzed legislations, where despite seeing that the indigenous educational theme has been developed in today’s society, there is still much to be done, both from the legal point of view as practical.